2019
DOI: 10.1039/c9em00241c
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous film forming foam and associated perfluoroalkyl substances inhibit methane production and Co-contaminant degradation in an anaerobic microbial community

Abstract: This work determines the components of aqueous film forming foam responsible for disrupting microbial community functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Fitzgerald et al [ 2 ] reported that PFOS at a concentration of 50 mg L −1 was inhibitory to mixed anaerobic cultures from a seed digester, using sludge as electron donor. In this study, in the first 3 days of assay, a significantly reduction of the CH 4 production rate by the action of PFOS was observed, compared with the control without PFAS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fitzgerald et al [ 2 ] reported that PFOS at a concentration of 50 mg L −1 was inhibitory to mixed anaerobic cultures from a seed digester, using sludge as electron donor. In this study, in the first 3 days of assay, a significantly reduction of the CH 4 production rate by the action of PFOS was observed, compared with the control without PFAS.…”
Section: Resultsmentioning
confidence: 99%
“…PFAS, including per- and polyfluoroalkyl substances, are organofluorine compounds highly used in several industrial sectors for applications such as oil production, refrigerators, firefighting foams, textiles, and stain resistance products, among others [ 1 , 2 ]. These compounds are known to pose environmental and human health risks due to their wide distribution, recalcitrant behavior, bioaccumulation tendencies, and potential toxicological effects [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, methane production was observed to be enhanced in the presence of PFOS [62], and results suggested that PFOS may act as metabolic decouplers. Conversely, PFAS-containing AFFFs have been reported to inhibit both methane production and co-contaminant degradation in an anaerobic microbial community [63]. This remains an area of intense research activity because the potential presence of PFAS volatiles in biogas raises concerns regarding the further spread of PFAS via atmospheric routes [64].…”
Section: Pfas Volatiles In Landfill Gaseous Emissionsmentioning
confidence: 99%
“…Microbial community metabarcoding tools and quantitative polymerase chain reaction have been applied in an effort to correlate changes in microbial community structures to PFAS contamination in order to form hypotheses about the main microbial players involved in PFAS transformations (Bao et al 2018;Fitzgerald et al 2019;Ke et al 2020;O'Carroll et al 2020;Zhang et al 2019aZhang et al , b, 2020. O'Carroll et al (2020) observed an increase in the relative abundance of Gordonia spp.…”
Section: Introductionmentioning
confidence: 99%